Intonaspacio : comprehensive study on the conception and design of digital musical instruments : interaction between space and musical gesture - Rodrigues, Mailis Gomes (2017)
Site-specific art understands that the place where the artwork is presented cannot be excluded from the artwork itself. The completion of the work is only achieved when the artwork and place intersect. Acoustically, sound presents a natural relation with place. The perception of sound is the result of place modulation on its spectral content, likewise perception of place is dependent on the sound content of that place. Even so, the number of sound artworks where place has a primary role is still very reduced. We thus purpose to create a tool to compose inherently place-specific sounds. Inherently because the sound is the result of the interaction between place and performer. Place because is the concept that is closer to human perception and of the idea of intimacy. Along this thesis we suggest that this interaction can be mediated by a digital musical instrument - Intonaspacio, that allows the performer to compose place-specific sounds and control it. In the rst part we describe the process of construction and design of Intonaspacio - how to access the sound present in the place, what gestures to measure, what sensors to use and where to place them, what mapping to design in order to compose place-speci c sound. We start by suggesting two di erent mappings to combine place and sound, where we look at di erent approaches on how to excite the structural sound of the place, i.e., the resonant frequencies. The rst one, uses a process where the performer can record a sample of sound ambiance and reproduce it, creating a feedback loop that excites at each iteration the resonances of the room. The second approach suggest a method where the input sound is analyzed and an ensemble of the frequencies of the place with the highest amplitudes is extracted. These are mapped to control several parameters of sound e ects. To evaluate Intonaspacio we conducted an experiment with participants who played the instrument during several trial sessions. The analysis of this experiment led us to propose a third mapping that combines the previous mappings. The second part of the thesis intends to create the conditions to give longevity to Intonaspacio. Starting from the premise that a musical instrument to be classi ed as such needs to have a dedicated instrumental technique and repertoire. These two conditions were achieved first, by suggesting a gestural vocabulary of the idiomatic gestures of Intonaspacio based on direct observation of the most repeated gestures of the participants of our experiment. Second, by collaborating with two composers whom wrote two pieces for Intonaspacio.